2017
DOI: 10.15171/jnp.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of hydroalcoholic extract of Lavandula officinalis L. on cyclophosphamide-induced nephrotoxicity in mice

Abstract: Background: Cyclophosphamide (CP) is amongst the most effective alkylating anticancer drugs which regardless of its harmful side effects including nephrotoxicity, hematotoxicity, mutagenicity and also immunotoxicity, commonly raised for the treatment of a number of cancers and autoimmune ailments. Objectives: This study was undertaken to investigate the ameliorative effect of Lavandula officinalis L extract (LOE) in nephrotoxicity induced by CP in mice. Materials and Methods:In this experimental study, 35 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Measuring blood levels of enzymes, biochemicals are important for indication of damage to any tissue. High levels of any factor may connote a fracture of active pathologies (21,22). Also, in this study, increasing Cr and BUN levels in MMI-treated group demonstrated renal toxicity (P < 0.001), which may possibly be due to damage generated in kidney tubules in comparison to the control group.…”
Section: Discussionmentioning
confidence: 47%
“…Measuring blood levels of enzymes, biochemicals are important for indication of damage to any tissue. High levels of any factor may connote a fracture of active pathologies (21,22). Also, in this study, increasing Cr and BUN levels in MMI-treated group demonstrated renal toxicity (P < 0.001), which may possibly be due to damage generated in kidney tubules in comparison to the control group.…”
Section: Discussionmentioning
confidence: 47%